Communication in the leading process: its importance for "engagement" in the workplace (Research, Society and Development, 2021)
Introduction: The work process goes through constant changes related to the environment, the organization, the dynamics and the perception of work by the professional himself. Thus, when communication does not occur in an assertive way, it can bring several losses in this process of change. Objective: To identify the importance of communication in the leadership process for “engagement” in the work environment and its impact on professional productivity. Methodology: This is an integrative literature review, exploratory, descriptive, with a qualitative approach, which used articles, dissertations and theses published between 2016 and 2020. The materials were extracted from SciELO, Google Scholar, Virtual Library of Fundação Getúlio Vargas and institutional repositories. Theoretical Discussion: The studies that make up the theoretical discussion were organized into categories that discuss the importance of communication in the work process; the main characteristics of the leader today and his relationship with engagement; and the influence of engagement in the performance of leaders and followers. Final Considerations: Communication has a decisive influence on the performance of leaders and their collaborators, stimulates team engagement in addition to strengthening the links between team members, favoring productivity, individual and collective development.